Effect of Fertilizers and Neem Cake Amendment in Soil on Spore Germination of Arthrobotrys dactyloides - Kumar, D. (The Korean Society of Mycology, 2005)
Application of fertilizers such as urea, diammonium phosphate (DAP) and muriate of potash in soil adversely affected the spore germination of Arthrobotrys dactyloides. Amendment of soil with urea at the concentrations of 1.0%, 0.5% and 0.1% completely inhibited spore germination and direct trap formation on the conidium, whereas muriate of potash delayed and reduced the spore germination even at the lowest concentration. DAP also inhibited spore germination at 1.0% concentration, while at lower concentration the percentage of spore germination was reduced. Application of neem cake at the concentration of 0.5% also inhibited spore germination after 24 h of amendment. The inhibitory effect of neem cake was reduced after 15 days of amendment, while after 30 days after amendment the inhibitory effect was completely lost and the spore germinated by direct trap as in unamended soil. Nematodes were not attracted to ungerminated spores after 24 h of amendment. After 15 days of amendment nematodes were attracted to agar blocks containing fewer germinated spores after 24 h of incubation but after 48 h of incubation large number of nematodes were attracted and trapped by the germinated spores with direct traps. After 30 days of amendment, larger number of nematodes were attracted and trapped by direct traps.